2019
DOI: 10.1158/0008-5472.can-18-3855
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Ablation of the Cystine Transporter xCT in PDAC Cells Inhibits mTORC1, Growth, Survival, and Tumor Formation via Nutrient and Oxidative Stresses

Abstract: Although chemoresistance remains a primary challenge in the treatment of pancreatic ductal adenocarcinoma (PDAC), exploiting oxidative stress might offer novel therapeutic clues. Here we explored the potential of targeting cystine/glutamate exchanger (SLC7A11/xCT), which contributes to the maintenance of intracellular glutathione (GSH). Genomic disruption of xCT via CRISPR-Cas9 was achieved in two PDAC cell lines, MiaPaCa-2 and Capan-2, and xCT-KO clones were cultivated in the presence of N-acetylcysteine. Alt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
152
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(177 citation statements)
references
References 48 publications
15
152
1
Order By: Relevance
“…Depletion of glutathione by APR-246, which binds thiol-groups, in combination with inhibition of xCT could make cancer cells more vulnerable to oxidative stress. Accordingly, it may be necessary to increase oxidative stress to facilitate cell death in xCT ko cells [80,81]. This is consistent with the absence of xCT in genome-wide ko screens.…”
Section: Howsupporting
confidence: 77%
“…Depletion of glutathione by APR-246, which binds thiol-groups, in combination with inhibition of xCT could make cancer cells more vulnerable to oxidative stress. Accordingly, it may be necessary to increase oxidative stress to facilitate cell death in xCT ko cells [80,81]. This is consistent with the absence of xCT in genome-wide ko screens.…”
Section: Howsupporting
confidence: 77%
“…Moreover, the expression of SLC7A11 is upregulated in the pancreatic tumor tissues and pancreatic cancer cells can increase SLC7A11 expression in response to oxidative stress, which results in the increase in GSH synthesis and enables tumor cells to survive in the presence of elevated ROS (91). Recent studies demonstrated that genetic deletion of SLC7A11 induces PDAC cell and tumor ferroptosis, and PDAC cells can use cysteine to synthesize GSH and coenzyme A to down-regulate ferroptosis (92,93).…”
Section: Regulation Of Redox Balancementioning
confidence: 99%
“…To date, in vivo evidence for the role of system x c in cancer has largely relied on ex vivo assays, direct injection of chemical probes (19), or implantation of cells with existing alterations that could impact engraftment (20). In order to determine the reliance of established pancreatic tumors on system x c in a physiological context, we employed a dual recombinase genetic engineering strategy based on the wellvalidated "KPC" mouse (21 Figure 5 for more information) developed tumors histopathologically identical to those from KPC mice: typically a single, focal mass with moderate differentiation and robust stromal desmoplasia (Supplementary Figure 6A), in the context of surrounding premalignant histopathology (Supplementary Figure 6B).…”
mentioning
confidence: 99%